2019
DOI: 10.3390/ijerph16224323
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Atmospheric Culturable Bioaerosols at Mountain and Seashore Sites

Abstract: Concentrations of atmospheric culturable bioaerosols at mountain and seashore sites were measured in field investigations by using a bio-culture sampler. The eastern Korean peninsula was selected for the measurements because of the short distance between the mountain site and the seashore site. Detectable concentrations of culturable fungal and bacterial bioaerosols (maximum 1065 CFU/m3) were quantitatively measured at the mountain and seashore sites. In addition, measurement of bioaerosols was conducted at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Lee et al, 2019 conducted measurements of bioaerosols at sites in the mountains and at the seashore and used the data of an urban area as a reference. Their results showed lower values of bioaerosols at the seashore and urban sites than in the mountains sites [ 30 ]. The authors agree with Fröhlich-Nowoisky et al (2016) who reported that trees and other living organisms in the mountains could produce high amounts of bioaerosols [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al, 2019 conducted measurements of bioaerosols at sites in the mountains and at the seashore and used the data of an urban area as a reference. Their results showed lower values of bioaerosols at the seashore and urban sites than in the mountains sites [ 30 ]. The authors agree with Fröhlich-Nowoisky et al (2016) who reported that trees and other living organisms in the mountains could produce high amounts of bioaerosols [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mesophilic bacterial concentrations are not necessarily lower in mountain regions than in other areas. Lee et al (2019) found higher mesophilic bacterial concentrations of 7.8 × 10 2 CFU/m 3 in a mountain region of Korea than in the coastal area [ 30 ]. Furthermore, in the Qinling Mountains in China, the concentration of airborne cultivable mesophilic bacteria was of 3.8 × 10 3 ± 1.8 × 10 3 CFU/m 3 which was higher than those in the urban environment [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomonitoring was performed at 30 points in different wards in the hospital, such as the internal medicine, surgical ward, general ward, treatment rooms, patient rooms, and central supply room (CSR), in which equipment and medical instruments are sterilized and stored. Airborne bacteria and fungi were selected for measurement because they are the most representative bioaerosols in the general environment on the Korean Peninsula [ 15 , 16 ]. Particle numbers were also monitored in real-time in order to analyze the correlation between particle numbers and bioaerosol concentration.…”
Section: Methodsmentioning
confidence: 99%
“…16 Significantly higher concentrations of bacteria and fungi culturable bioaerosols were found at mountain site as compared to urban and seashore sites during April month in Korean Peninsula region. 17 Fungii were estimated as 805 102 and 75 CFU/m 3 at the mountain, urban and seashore sites respectively while bacteria were as 775, 232 and 150 CFU/m 3 at the mountain, urban and seashore sites respectively. Bacteria levels were drastically lower during February month at these sites.…”
mentioning
confidence: 95%